THE SEASONAL FLUCTUATIONS OF INFECTION AND SPERMACTIVITY IN THE TEMPERATE CLIMATE - Al-Janabi, Mohammed (Iraqi Journal of Science, 2024)
Widal and Rose Bengal tests were conducted for patients who were attending tothe High Institute of Infertility Diagnosis and Assisted ReproductiveTechnology/Al-Nahrain University and a private Laboratory during the years 2005-2007. Monthly variation in the incidence of infections and the number of motilesperms were studied. For Widal test a titer of 1:80 regarded as negative, and a titerof 1:160 and more considered positive for O and H antigens with visibleagglutination. Brucello-slide test was used to detect brucella–specific agglutinins.The positive sera for each of Brucella and Salmonella were 140 and1505, during theyears 2006, 2007and2005, 2006, 2007 respectively. The seminal fluid analyses wereevaluated separately for other 4398 patients during the years 2006-2007 to detect thenumber of motile sperms. The study revealed a significant difference between winterand summer, higher in summer than winter with respect to Brucellosis [p<0.05],Salmonillosis [p<0.0001]. In contrast, the number of motile sperms was higher inwinter than summer [p<0.01]. On the other hand, the study may refer to the presenceof a similar regular rhythm of the infections that take place and the vitality ofspermatozoa during different months of the year.